RUSSIAN EXPERTS’ CONSENSUS ON METABOLIC SYNDROME PROBLEM IN THE RUSSIAN FEDERATION: DEFENITION, DIAGNOSIS CRITERIA, PRIMARY PREVENTION AND TREATMENT - N. M. Achmegdanov; S. A. Butrusova; I. I. Dedov; L. A. Zvenigorodskaya; O. A. Kislyak; O. A. Koshelskaya; I. V. Kuznecova; V. V. Kuharchuk; A. Yu. Litvin; I. V. Medvedeva; A. M. Mkrtumyan; V. B. Mychka; et al. (Рациональная фармакотерапия в кардиологии)
Russian Experts’ Consensus on Metabolic Syndrome Problem in the Russian Federation: Defenition, Diagnosis Criteria, Primary Prevention and Treatment.